2018
DOI: 10.1007/s12011-017-1236-3
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Chromium Supplementation on Glycemic Control, Markers of Cardio-Metabolic Risk, and Oxidative Stress in Infertile Polycystic ovary Syndrome Women Candidate for In vitro Fertilization: a Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: This study was carried out to investigate the effects of chromium intake on glycemic control, markers of cardio-metabolic risk, and oxidative stress in infertile polycystic ovary syndrome (PCOS) women candidate for in vitro fertilization (IVF). This randomized double-blind, placebo-controlled trial was done among 40 subjects with infertile PCOS candidate for IVF, aged 18-40 years old. Individuals were randomly allocated into two groups to take either 200 μg/day of chromium (n = 20) or placebo (n = 20) for 8 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…The current research results also indicated that the dietary intake of Cr was lower in the PCOS patients with MetS when compared with those without MetS. Similarly, another research showed that 8 weeks of Cr application in infertile women with PCOS could have a positive impact on glycemic control, decline of fasting insulin, HOMA-IR, TG, VLDL and total cholesterol, increase of antioxidant capacity, and improvement of oxidative stress [19]. A review article stated that Cr supplement has limited impact on the weight loss, glucose control, lipid profile and hormonal disturbance of PCOS women [46].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The current research results also indicated that the dietary intake of Cr was lower in the PCOS patients with MetS when compared with those without MetS. Similarly, another research showed that 8 weeks of Cr application in infertile women with PCOS could have a positive impact on glycemic control, decline of fasting insulin, HOMA-IR, TG, VLDL and total cholesterol, increase of antioxidant capacity, and improvement of oxidative stress [19]. A review article stated that Cr supplement has limited impact on the weight loss, glucose control, lipid profile and hormonal disturbance of PCOS women [46].…”
Section: Discussionsupporting
confidence: 64%
“…Cr supplements are reportedly able to improve insulin sensitivity and MetS parameters in type 2 diabetic patients [ 18 ]. Cr supplementation can have useful impacts on glycemic control and improvement of CVD risk and oxidative stress state in PCOS patients [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of probiotics in regulating and rebuilding the host intestinal microbiome is well recognized, and the probiotic interference strategy has been used to prevent and cure various metabolic diseases, including type 2 diabetes (15), inflammatory bowel disease (IBD)/irritable bowel syndrome (IBS) (16), and hyperglycemia (17). Recently, the beneficial effects of probiotic supplementation on markers for insulin metabolism and some lipid profiles in women with PCOS were reported (18). Consequently, we hypothesized that the use of probiotics could relieve the symptoms of PCOS in patients through the regulation of the intestinal microbiome.…”
Section: Introductionmentioning
confidence: 99%
“… 79 Similar findings have been obtained for combined magnesium and zinc supplementation. 80 Jamilian et al 81 also reported that chromium administration in infertile women with PCOS, who were candidates for IVF, for eight weeks, had beneficial effects on glycemic control and OS. Various pharmacological studies have demonstrated that crocetin has a wide range of antioxidant, anti-cancer, hypolipidemic, and anti-atherosclerotic effects.…”
Section: Antioxidants In Pcosmentioning
confidence: 99%